Low Plasma Atherogenic Index Associated with Poor Prognosis in Hospitalized Patients with Acute Myocardial Infarction - Anggoro Budi Hartopo; Irsad Andi Arso; Budi Yuli Setianto (Interna Publishing, 2016)
Aim: the impact of atherogenic index of plasma (AIP), calculated as logarithmic of triglyceride:HDL ratio (log10.[TG:HDL]), on major adverse cardiovascular events (MACE) during acute myocardial infarction (AMI) has not been fully accepted. This study aims to investigate the role of AIP in predicting major adverse cardiovascular events following AMI during intensive care in the hospital. Methods: this was a prospective cohort study. We enrolled subjects with AMI hospitalized in intensive coronary care unit at Dr. Sardjito General Hospital, Yogyakarta. The AIP was measured in fasting blood within 24 hours of hospital admission. The total cholesterol, LDL, HDL, and triglyceride (TG), were measured and AIP value was determined as log10.[TG:HDL]). Based on AIP value, subjects were allocated into low AIP (<0.24) and high AIP (≥0.24). The outcome of the study was major adverse cardiovascular events during hospitalization, i.e. multipart of all cause mortality, acute heart failure, cardiogenic shock, reinfarction, and rescucitated VT/VF. Results: among 277 subjects, the high AIP group comprised 213 subjects (77%) and low AIP group comprised 64 subjects (33%). During intensive hospitalisation, 66 subjects (24%) developed MACE and 20 subjects (7%) developed fatal outcome (all cause mortality). The incidence of MACE tended to be higher in low AIP group, however its difference was not significant. The incidence of all cause mortality was significantly higher in low AIP group (14%) than in high AIP group (5%). Multivariable analysis showed that low AIP predicted all cause mortality independently with a risk ratio 3.71 (95% CI 1.26 - 10.97, p=0.02). Conclusion: low AIP value (<0.24) is an independent predictor for all cause mortality in patients with acute myocardial infarction undergoing intensive hospitalisation.